2018
DOI: 10.1080/23328940.2018.1468205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of solar radiation on pediatric heat balance within enclosed, hot vehicles

Abstract: Pediatric deaths due to children being left in hot cars remain a significant yet preventable public health concern. The current study aims to demonstrate the influence of vehicle type, time of day, and solar exposure (sun or shade) on the energy balance and core temperature (Tc) of a hypothetical two-year old boy left in a vehicle on a hot day. Cabin temperatures and relative humidity were collected within six enclosed vehicles under sun or full shade in Tempe, Arizona. These variables and radiation estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Based on the limited information available in the Ford Motor Company press release, it is not possible to make a direct comparison between this study and the approach employed in Ford Police Interceptor Utility vehicles, yet our data support the use of active heating as a means to reduce the infectivity of SARS-CoV-2 on surfaces in vehicle interiors. Numerous studies have demonstrated the potential for passive heating of passenger cars to very high temperatures in as little as an hour when parked in sunlight with the windows up, although the final temperatures reached were dependent on the ambient temperature (McLaren et al 2005 ; Grundstein et al 2009 ; Vanos et al 2018 ). Sunlight plays an important role in this heating process when short wave solar radiation transmitted through windows onto interior surfaces is partially reflected as long-wave thermal radiation, which effectively becomes trapped within the vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the limited information available in the Ford Motor Company press release, it is not possible to make a direct comparison between this study and the approach employed in Ford Police Interceptor Utility vehicles, yet our data support the use of active heating as a means to reduce the infectivity of SARS-CoV-2 on surfaces in vehicle interiors. Numerous studies have demonstrated the potential for passive heating of passenger cars to very high temperatures in as little as an hour when parked in sunlight with the windows up, although the final temperatures reached were dependent on the ambient temperature (McLaren et al 2005 ; Grundstein et al 2009 ; Vanos et al 2018 ). Sunlight plays an important role in this heating process when short wave solar radiation transmitted through windows onto interior surfaces is partially reflected as long-wave thermal radiation, which effectively becomes trapped within the vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…The first is that by increasing the test temperature from room temperature we can shorten the required experiment time. The second is that the interior temperature of a vehicle parked under the sun can easily reach 40 °C [9].…”
Section: Emission Profile Of Triethylphosphate In Chamber Testsmentioning
confidence: 99%
“…Although the tests were carried out at 40 °C, emissions of TEP at lower temperatures may also be expected. Our results are considered relevant to reallife exposures, as car seats are subjected to a wide temperature range during use in various weather conditions [9].…”
Section: Influence Of Emissions Of Opfrs From Car Seats On Indoor Air...mentioning
confidence: 99%
“…12 This recommendation is especially concerning since reports have shown that car dashboard surface temperatures can reach up to 69°C (156°F) after sitting in the sun for only an hour, and that automobile glove compartment chambers can reach temperatures exceeding 66°C (150°F). 13,14 The naloxone nasal spray device has become the preferred delivery system for the lay community, law enforcement, and fire personnel due to ease of use. Exposure to these extreme temperatures outside the recommended range may negatively impact delivery of naloxone through the device to the patient.…”
Section: Introductionmentioning
confidence: 99%